A New Insight on the Role of the Cerebellum for Executive Functions and Emotion Processing in Adults - Beuriat, Pierre-Aurélien; Cohen-Zimerman, Shira; Smith, Gretchen N. L.; Krueger, Frank; Gordon, Barry; Grafman, Jordan (Frontiers in Neurology, 2020)
Objective: We investigated whether the cerebellum plays a critical or supportive role in in executive and emotion processes in adults. Many investigators now espouse the hypothesis that participants with cerebellar lesions experience executive functions and emotions (EE) disorders. But we hypothesized that these disorders would be milder if the damage is relatively limited to the cerebellum compared to damage involving the cerebellum plus additional cortical areas. Methods: We studied veterans with penetrating Traumatic Brain Injury (pTBI) participating in the Vietnam Head Injury Study (VHIS). We selected veterans with a cerebellar lesion (n = 24), a prefrontal cortex lesion (n = 20), along with healthy controls (HC) (n = 55). Tests of executive functions and emotions were analyzed as well as caregiver burden. We performed between-group null hypothesis significance testing, Bayesian hypothesis tests and correlational analyses. Results: Performance of participants with cerebellar lesions which extended to the cerebral cortex was similar to the HC on the Executive Function tests but they were significantly impaired on the Working Memory Index. No differences were found on the emotional processing tasks with one exception—the Facial Expression of Emotion-Test (FEEST). We then examined a sub-group of participants with large cerebellar lesions (>15%) but minimal lesions in the cerebral cortex (<15%). This sub-group of participants performed similarly to the HC on the Working Memory Index and on the FEEST. Conclusions: We suggest that the cerebellar cortex may not be critical for executive functions or processing emotional stimuli in adults as suggested. Instead, we find that the cerebellum has a supportive role characterized by its computing of the motor requirements when EE processing is required.